THE EFFECT OF NUTRITION EDUCATION WITH SOCIAL MEDIA ON CHANGES IN KNOWLEDGE AND DIET QUALITY IN OBESITY WOMEN - Emilia Alfitri; Ratih Kurniasari (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background: Obesity in women is higher than in men. Changes in women's weight loss are influenced by many factors: nutritional knowledge and the quality of a healthy diet. The provision of nutrition education can use various media such as social media, which is currently many people, especially women. Research Methods: This study uses the literature review method by searching for journals through the Google Scholar portal with the SINTA index. Research Result: How is the effect of nutrition education with social media such as (Instagram and Whatsapp Group) on increasing nutritional knowledge in Obese Women. Conclusion: There is an effect of nutrition education with social media such as (Instagram and Whatsapp Group) on increasing nutritional knowledge, but not all of them can change diet quality behavior because to change diet quality requires encouragement, namely motivational interviewing and a long period of mentoring.